ProNGF and Neurodegeneration in Alzheimer’s Disease - Fahnestock, Margaret; Shekari, Arman (Frontiers in Neuroscience, 2019)
Profound and early basal forebrain cholinergic neuron (BFCN) degeneration is a hallmark of Alzheimer’s disease. Loss of synapses between basal forebrain and hippocampal and cortical target tissue correlates highly with the degree of dementia and is thought to be the primary mechanism of memory loss. BFCNs depend for their survival, connectivity and function on the neurotrophin nerve growth factor (NGF) which is retrogradely transported from its sites of synthesis in cortex and hippocampus. The form of NGF found in human brain is proNGF. ProNGF binds to the NGF receptors TrkA and p75NTR, but it binds more strongly to p75NTR and more weakly to TrkA than does mature NGF. This renders proNGF more sensitive to receptor balance than mature NGF. In healthy brain, where BFCNs express both TrkA and p75NTR, proNGF is neurotrophic, activating TrkA-dependent signaling pathways such as MAPK and Akt-mTOR and eliciting cell survival and neurite outgrowth. However, if TrkA is lost or if p75NTR is increased, proNGF activates p75NTR-dependent apoptotic pathways such as JNK. This receptor sensitivity serves as a neurotrophic/apoptotic switch that eliminates BFCNs that cannot maintain TrkA/p75NTR balance and therefore synaptic connections with their targets. TrkA is increasingly lost in mild cognitive impairment (MCI) and Alzheimer’s disease. In addition, proNGF accumulates at BFCN terminals in cortex and hippocampus, reducing the amount of trophic factor that reaches BFCN cell bodies. The loss of TrkA and accumulation of proNGF occur early in MCI and correlate with cognitive impairment. Increased levels of proNGF and reduced levels of TrkA lead to BFCN neurodegeneration and eventual p75NTR-dependent apoptosis. In addition, in Alzheimer’s disease BFCNs suffer from reduced TrkA-dependent retrograde transport which reduces neurotrophic support. Thus, BFCNs are particularly vulnerable to Alzheimer’s disease due to their dependence upon retrograde trophic support from proNGF signaling and transport.